Gambaran Pengetahuan Remaja Putri tentang Makanan yang Kaya Zat Besi (Fe) untuk Pencegahan Anemia - Fathul Husni Syofyan; Ganis Indriati; Widia Lestari (Caring : Jurnal Keperawatan, 2021)
Background: Teenager especially girls are vulnerable for its disease because the need increasing of zinc level at puberty age, having blood loss at their period time and low zinc consumption. Anemia is a condition in which erythrocytes number (red blood cells) in the body is less than normal. Purpose: The purpose of this research was to describe the knowledge of female students in Agriculture Vocational High School Pekanbaru about high zinc foods consumption for anemia prevention. Method: The study conducted as a simple observational. There were of 64 respondent as sample taken by stratified random sampling and questionnaire data collecting that had registered validity and reliability. Result: The result showed that the students mostly were in the age of seventeen. The number of students were thirty students (48.4%) and the number of First Grade Student were thirty eight (59.4%). Respondent’s had good knowledge about iron food for the prevention of anemia is 67.2% and respondent’s had sufficient knowledge is 32.8%. Conclusion: The knowledge of teenager girls about high zinc foods for anemia prevention generally is good. This research is expected to give benefits to teenagers about the importance of consuming zinc food containing for the prevention of anemia.